Infectious diseases associated with pediatric type 1 diabetes mellitus: A narrative review - Piccolo, Gianluca; De Rose, Elena Lucia; Bassi, Marta; Napoli, Flavia; Minuto, Nicola; Maghnie, Mohamad; Patti, Giuseppa; d’Annunzio, Giuseppe (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) has been frequently associated with an impaired immune response against infectious agents, making affected patients at risk for more severe disease and sometimes causing worse outcomes. The recent COVID-19 pandemic has seriously affected patients with both diabetes, in particular those carrying comorbidities or with poor glycemic control. As regards pediatric diabetes mellitus, the availability of more accurate and technological tools for glycemic management and the improved markers of metabolic control might mitigate the negative impact of infections. Notably, good metabolic control of diabetes since its diagnosis reduces not only the risk of microangiopathic complications but also of impaired immune response to infectious diseases. Therefore, vaccinations are strongly recommended. Our paper aims to provide the most updated evidence regarding infectious diseases in type 1 pediatric DM.